ANALYSIS OF SULFUR VAPOR EXPOSURE TO THE NUMBER OF MICRONUCLEUS AND ORAL BUCCAL EPITHELIAL MORPHOLOGY - Rizki Amalina; Aulia Rohmania; Anggun Feranisa (FKG Unlam, 2020)
Background: The sulfur vapor consists of SO2 and CO2 which are genotoxins that may cause the damage of DNA to the micronucleus in buccal epithelial cells. Micronucleus is a mass like a nucleus, measuring one-third of the nucleus. DNA damage can also be seen from changes in the morphology of epithelial cells. Objective: This study aimed to identify the effect of sulfur vapor exposure on the number of micronucleus and morphology epithelial cells in the oral cavity on the sulfur miner. Methods: The method of this study was analytic observational with a cross-sectional approach. The total sample of this study was 24 respondents divided into 2 groups, each group contained 12 respondents. Exfoliated buccal cells were collected by scrapping the buccal mucosa. The specimens stained using Hematoxylin and Eosin. Nucleus and cytoplasmic area were examined using image J 1.40 Results: The result showed the average number of buccal mucosa micronucleus on coal miners higher (35,50) than controls (11,58). The result of Independent-measures T-test obtained significant different on the number of micronucleus between sulfur miner and controls (p=0,000). The result of Independent-measures T-test on the nuclear area and cytoplasmic area between sulfur miner and controls obtained insignificant different (p=0,379 dan p=0,616). Conclusion: Based on this study can be concluded that sulfur vapor exposure affected on the number of micronucleus on sulfur miners, but did not influence morphology of epithelial cells.